Accidental Ingestion of Local Anesthetic Solutions in Children - Afrouz Alipour; Sara Shokooh Saremi; Mohammad Reza Navaeifar (Mazandaran University of Medical Sciences, 2019)
Introduction: Anesthetic medications are frequently used in medical procedures to prevent pain and undesired sensations. Local anesthetic agents are widely used in the form of ointment, gel, cream, drop or spray in minor surgical or in-house pain relieving procedures in children and adults.  Case Presentation: A 16-month-old boy ingested an unknown amount of lidocaine and became lethargic after about 15 minutes. After a while, he experienced a generalized tonic-clonic seizure and loss of consciousness. He needed a short course of intubation and mechanical ventilation. A short literature review was also performed on local anesthetic intoxication. Conclusions: Safe-seeming local anesthetic agents can cause life-threatening complications, especially when used at home without enough medical knowledge or supervision.